Digital Media To Improve Children’s English Pronunciation: A Case Study - Chandra, Jenifer; Djuan, Devgandi; Shieren, Ruth (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Media gives children the opportunity to access any English-related contents to watch, listen to, and read. The easy access to media support children’s ability in learning a foreign language. By applying a qualitative approach, this paper aims to examine how media support children’s English pronunciation. The data were obtained from interviews and pronunciation tests. The results show the use of digital media improves children’s English pronunciation. The level of progress in English pronunciation accuracy is supported by the length of time children are exposed to digital media with English content. The inaccuracies in the pronunciation of English words are caused by pronunciation habits in their mother tongue (Indonesian). It is concluded that the critical age and the appropriate length of exposure to digital media with foreign language content greatly determine the ability to pronounce English words as a foreign language.